The Effect of Send- A problem Strategy in Acquiring Methods of teaching Concepts and Developing Teamworking Competency of Higher Education Students - Haji, Sattar Jabbar (Journal of Educational and Psychological Sciences, 2023)
The research aims to find out the effect of send- a problem strategy on acquiring the concepts of teaching methods and developing teamwork competency among students of the fourth-grade students at University of Zakho, in the second semester of the academic year 2022-2023. The researcher used the experimental design for two equal samples, the research sample included (41) male and female students, from the Department of Islamic studies, fourth grade, distributed into two groups, after random selection, the experimental group (A) became the number of its students (20) students, taught according to send- a problem strategy. And group (B) became the control, the number of its students was (21) male and female students, who taught according to the usual method. To achieve the objectives of the research, the researcher used two tools, the first is a test to acquire the concepts of teaching methods that he prepared, consisting of (20) items, and the second is a scale for measuring teamwork competency, consisting of (30) items, distributed over (9) domains. The psychometric properties of the two tools were verified. After completing the experiment and applying the two tools, the statistical analysis of the data was conducted using the t-test for paired sample, and independent samples. The results showed that the students of the experimental group outperformed the students of the control group in acquiring concepts of teaching methods and developing teamwork competency, and in the light of the research results, the researcher made several recommendations, introducing the theoretical and practical framework of send – a problem strategy in the content of the subject of teaching methods in general for the faculties of education and basic education in the universities of the Kurdistan Region of Iraq. Recommending the development of students’ teamwork competency, because of its positive impact on the development of students’ social skills and teamwork, which may be reflected in their personal and social lives in the post-university stage.